GLOBAL ISSUES OF ENVIRONMENTAL LAW ENFORCEMENT IMPACTS ON SUSTAINABLE DEVELOPMENT - ., Sopian; Pudjiastuti, Sri Rahayu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The global environmental crisis is caused by wrong and failed policies, low political commitment, deviant behavior from state actors ranging from trans-national corporations, consumerism and individualism culture, which ultimately harms the environment. The purpose of this research is to analyze environmental law, the form and importance of law enforcement in realizing sustainable development. The method used in this paper is to use a normative juridical approach. The results of the research show that currently environmental law is still weak in overcoming various environmental problems that occur. The cause of not optimal environmental law is the lack of a firm and real form of law enforcement. Therefore, law enforcement must be enforced for the realization of sustainable development